First measurement of Ds1(1+)(2536)+ and Ds2*(2*)(2573)* production in proton-proton collisions at √s=13 TeV at the LHC - Acharya, S.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (AMER PHYSICAL SOC, 2025)
The production yields of the orbitally excited charm-strange mesons D(s1()1(+))(2536)(+) and D-s2*(2*)(2573)* were measured for the first time in proton-proton (pp) collisions at a center-of-mass energy of root s = 13 TeV with the ALICE experiment at the LHC. The D-s1(+) and D-s2*(+) mesons were measured at midrapidity (|y| <0.5) in minimum-bias and high-multiplicity pp collisions in the transverse-momentum interval 2 < p(T) <24 GeV/c. Their production yields relative to the D-s(+) ground-state yield were found to be compatible between minimum-bias and high-multiplicity collisions, as well as with previous measurements in e(+/-)p and e(+)e(-) collisions. The measured D-s1(+)/D-s(+) and D-s2*(+) /D-s(+) yield ratios are described by statistical hadronization models and can be used to tune the parameters governing the production of excited charm-strange hadrons in Monte Carlo generators, such as PYTHIA 8.
Keywords: CHARM-STRANGE MESONS; PP COLLISIONS; EXCITED CHARM; Astronomy & Astrophysics; Physics